(untitled) (Anwer Khan Modern Medical College Journal, 2020)
A 6 years and 6 month old child hailing from Dhaka admitted into AKMMCH with the complaints of abdominal pain for 3 days and vomiting for 1 day. Abdominal pain was in umbilical region, severe, colicky, non-radiating and aggravated after taking meal. Patient’s mother also complained about vomiting for 1 day, 3-4 times, contained ingested food particle and associated with anorexia. Patient did not pass the stool for 1 day. Patient was infested with Ascaris lumbricoids 6 months back. On examination vitals were normal, abdomen was soft and tender, there was ill defined lump present in right iliac fossa, firm in consistency, adhere to underlying structures and free from overlying skin. So it is clinically diagnosed as a case of intestinal obstruction with appendicular lump. Further investigations confirmed that it is a case of intestinal obstruction due to worm bolus. AKMMC J 2020; 11(2) : 140-144